Barley Growth and Metals Accumulation in Salt-affected Mudflat Amended by Sewage Sludge. Issue 12 (4th July 2022) - Zuo, Wengang; Shen, Ziyi; Tang, Zehui; Lv, Ming; Ding, Cheng; Gu, Chuanhui; Bai, Yanchao; Shan, Yuhua; Dai, Qigen
ABSTRACT: Barley cultivation in salt-affected mudflat can alleviate the growing domestic barley demand and land use conflict. However, the coincidence of barley growing season and salt accumulation period of mudflat limits barley production despite of some natural tolerance to salt stress of barley plant. Sewage sludge can be used as organic modifier for mudflat amendment. In this study, a field experiment was conducted with one-time different sludge input rates to assess the responses of soil fertility factors, barley growth, and accumulation and uptake of metals in soil and barley plant to sewage sludge addition (SSA). The results showed that SSA improved soil physicochemical properties. The biomass and yield of barley grown in sludge-amended mudflat were elevated and the maximum increments were associated with 250 t ha −1 SSA rate. The concentrations of total and available cadmium (Cd), chromium (Cr), copper (Cu), nickel (Ni), lead (Pb), and zinc (Zn) increased in sludge-amended mudflat soil, and SSA rate was the major factor influencing metal concentrations. Sludge addition increased metal concentrations in barley plant, and metals uptake by barley plant were mainly accumulated in barley root. In summary, barley cultivation with relatively high yield and controllable metals risk in salt-affected mudflat can be achieved under one-time sludge addition even in salt accumulation period.